An Observational Cohort Study to Estimate the Durability of Humoral Immune Responses to Vaccination with ChAdOx1 nCoV-19 and the BBV152 in Adult Patients with Autoimmune Rheumatic Diseases (AIRD) - Ravi Kumar; Ramya Madhavan; John Mathew; Ashish Mathew; Ruchika Goel (Journal of Clinical Rheumatology and Immunology)
Background The durability of immune responses after vaccination against SARS CoV-2 in patients with autoimmune rheumatic diseases (AIRD) is not well studied. Objective We aimed to determine the longevity of humoral immune response to homologous vaccination with 2 doses of ChAdOx1 nCoV-19 and BBV152 in adult patients with AIRD. Methods In this prospective observational study, patients aged 18 to 60 years, diagnosed with SLE, primary systemic vasculitis and inflammatory arthritis (IA) who were scheduled to or had received vaccination with either ChAdOx1 nCoV-19 or BBV152 were recruited between June 2021 to March 2023. IgG antibodies against SARS CoV-2 spike protein (anti-S) were estimated in serum or plasma of patients prior to vaccination if feasible (T0), 15 to 28 days (T1), 75-100 days (T2), 170-190 days (T3), 240-290 days (T4), 340-370 days (T5) after receiving Vx2 by Diasorin chemiluminescence assay. The association of antibody titers with baseline parameters is estimated using chi-square or Mann Whitney tests using SPSS 16. Results Overall, 118 patients (93 females; age: 37.1, IQR: 28- 45 years; disease duration: 60 ((IQR) 29-103) months) with AIRD (SLE:48(40.6%), IA:53(44.9%), systemic vasculitis:7(5.9%) and spondyloarthropathy: 9(7.6%)) were recruited. Baseline demographic data has been depicted in (Table 1). The median antibody titer did not differ significantly between the two vaccines at T1 while the titers at T2, T3 and T4 were significantly lower for those vaccinated with BBV 152 (Table 2). The steroid dose prior to T1 and T2, intake of DMARDs in peri-vaccination period, type of AIRD (IA vs CTD) was not associated with significant difference in antibody titers at T1 and T2. Conclusion The anti-S humoral immune response persisted beyond 1 year for most of our patients with AIRD. After 3 months of vaccination, these responses were higher for ChAdOx1 nCoV-19 as compared with BBV152 in our patients with AIRD.